2019
DOI: 10.33549/physiolres.933952
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of endothelial transient receptor potential vanilloid type 4 channel underlines impaired endothelial nitric oxide-mediated relaxation in the mesenteric arteries of hypertensive rats

Abstract: The endothelium contributes to the maintenance of vasodilator tone by releasing endothelium-derived relaxing factors, including nitric oxide (NO). In hypertension, endothelial nitric oxide synthase (eNOS) produces less NO and could be one of the contributing factors to the increased peripheral vascular resistance. Agonist-induced Ca(2+) entry is essential for the activation of eNOS. The transient receptor potential vanilloid type 4 (TRPV4) channel, a Ca(2+)-permeant cation channel, is expressed in the endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…In accord with our findings, Boudaka et al (2019) reported decreased expression of endothelial TRPV4 and impaired endothelium-dependent vasorelaxation in second-order branches of the mesenteric arteries of 10- to 12-week-old SHR, although some disparities exist between the two studies. While the downregulation of endothelial TRPV4 led to a loss of NO in the Boudaka et al (2019) study, the downregulation of endothelial TRPV4 led to a loss of EDH in our study. The reason for the disparity is not clear, but it might be related to the differences in strain, age, or vessel diameter used.…”
Section: Trpv4 and Hypertensionsupporting
confidence: 91%
“…In accord with our findings, Boudaka et al (2019) reported decreased expression of endothelial TRPV4 and impaired endothelium-dependent vasorelaxation in second-order branches of the mesenteric arteries of 10- to 12-week-old SHR, although some disparities exist between the two studies. While the downregulation of endothelial TRPV4 led to a loss of NO in the Boudaka et al (2019) study, the downregulation of endothelial TRPV4 led to a loss of EDH in our study. The reason for the disparity is not clear, but it might be related to the differences in strain, age, or vessel diameter used.…”
Section: Trpv4 and Hypertensionsupporting
confidence: 91%
“…Dilation of leptomeningeal arteries occurs as early as 6 h after pMCAO via increased phosphorylation of endothelial nitric oxide synthase (eNOS) in response to shear stress (Iwasawa et al, 2018). Meanwhile, Trpv4 −/− mice exhibited loss of shear stress-induced vasodilatation of the carotid artery (Hartmannsgruber et al, 2007), and endothelial downregulation of TRPV4 was shown to contribute to impairment of eNOS-mediated relaxation of the mesenteric artery (Boudaka et al, 2019). These findings suggest that TRPV4 deficiency may exacerbate ischemic brain injury through impairment of acute collateral development in cases of recanalization failure, such as the pMCAO model.…”
Section: Discussionmentioning
confidence: 99%
“…In INS-1E pancreatic β cells, 4α-PDD treatment increases intracellular Ca 2+ levels and enhances glucose-stimulated insulin secretion (Skrzypski et al 2013). Furthermore, in rodents, 4α-PDD induces endothelial-dependent NO-mediated relaxation in the mesenteric arteries (Boudaka et al 2019). 4α-PDD treatment elicits the dilation of mesenteric arteries in aged rats by increasing intracellular Ca 2+ levels (Du et al 2016).…”
Section: Exogenous Agonistsmentioning
confidence: 99%